Observation of fractional spin textures in a Heusler material - Jagannath Jena; Börge Göbel; Tomoki Hirosawa; Sebastián A. Díaz; Daniel Wolf; Taichi Hinokihara; Vivek Kumar; Ingrid Mertig; Claudia Felser; Axel Lubk; Daniel Loss; Stuart S. P. Parkin (Nature Communications, 2022)
Skyrmions and anti-skyrmions are magnetic textures that have garnered much interest due to their stability. Here, Jena et al demonstrate the existence of fractional spin textures at the edges of Heusler alloy sample, which can have continuous variable topological charges.